FENOMENA CHILDFREE PADA PASANGAN MUDA DI DAERAH KOTA CIREBON DITINJAU BERDASARKAN HUKUM KELUARGA ISLAM - Asep Saepullah; Ahmad Rofi'i; Putri Berlian Sari (Mahkamah : Jurnal Kajian Hukum Islam, 2023)
The childfree phenomenon has emerged on a global scale. The childfree phenomenon itself has existed since the 1500s in several countries such as France, England and the Netherlands. However, the term childfree appeared in Indonesia beginning with a statement by a public figure on his social media account, who declared himself an adherent of the childfree principle (married without having children). And along with the times, the human mindset also developed. Having children is not an obligation, rather a life choice and mutual agreement between husband and wife. This phenomenon is not only contrary to the noble values of the nation's culture, it becomes a little confusing when it occurs within the body of Muslims, bearing in mind that from a young age Muslims have been instilled with the understanding that marriage is a way to perfect religion and one of the missions marriage is to have godly offspring. This study aims to answer the questions that form the formulation of the problem: "What is the understanding/response of young couples in the city of Cirebon to the childfree phenomenon and what is the review of Islamic family law towards the childfree phenomenon?". This study uses qualitative research, data collected by means of interviews (interviews) observation, documentation and then analyzed by descriptive analysis method. The results of this study: Young couples in the city of Cirebon do not agree with the implementation of voluntary childfree because it is not appropriate both in terms of culture and religion in Indonesia, especially Islam. Because one of the goals of marriage in Islamic law is to protect offspring. However, some young couples in the city of Cirebon implement temporarily childfree which does not conflict with the noble culture and religion in Indonesia. Because temporarily childfree only aims to delay, not unfairly, having children in marriage. In Islamic law, this is permissible because it has the same goal as Tandzim al-Nasl, namely to prosper the life of the nation and religion, so that good generations are created for the future. Therefore, this is not against Islamic family law because the intention is to produce a good generation.